An exploratory study of neighbourhood heterogeneity in health: evidence from China. Issue 10 (2nd October 2020) - Gu, Lijuan; Yang, Linsheng; Wang, Li; Yu, Jiangping; Wei, Binggan
ABSTRACT: A systematic understanding of the potential contribution of the neighbourhood in explaining health inequalities remains an under-researched area. To quantify the importance of the neighbourhood in explaining health, by conducting pooled cross-sectional investigations of 49, 602 adult participants, this study has hierarchically examined the magnitude of neighbourhood heterogeneity in different health outcomes in five Chinese provinces from 2010 to 2016. We found significant neighbourhood heterogeneity in both self-reported health and mental health with neighbourhood explaining 2.37% to 22.7% of the total variance. The majority of neighbourhood heterogeneity remained significant, with a range between 2.66% to 19.16% after individual attributes were considered. The magnitudes of neighbourhood heterogeneity in health were different across provinces, with Guangdong being the highest, followed by Shanghai and Henan, followed by Gansu and ended by Liaoning. There was a slightly descending trend in neighbourhood heterogeneity in health from 2010 to 2016. There remained unexplained significant and increased spatiotemporal variations in neighbourhood heterogeneity in health, after neighbourhood socioeconomic and sociodemographic attributes were considered. Both the compositional and contextual factors of neighbourhood heterogeneity in health were conditional on broader contextual backgrounds. Our study is the first of its kind in systematically investigating neighbourhood heterogeneity in health using provincially representative data from China's national database. Our findings have strengthened the groundwork for studies linking the neighbourhood to health and provided the framework for future studies to assess neighbourhood heterogeneity in health in consideration to broader contexts.